Indirect Construction of Hedonic Price Indexes for Private Properties - Stefan Sebastian Fahrländer (Swiss Journal of Economics and Statistics, 2008)
This paper analyzes the construction of price indexes for condominiums and single family houses in Switzerland over the period 1985 to 2004 using the indirect method. We find, that the pooling of the data, i.e. direct indexes with fixed hedonic prices, are good models for average properties but can be biased for the indexation of non-average properties. Therefore indirect index construction using predictions for specific properties based on annual equations is recommended. Based on differentiation of forty regions it is shown, that indexes vary from region to region, but show a comparable general path between 1985 and 2004. In recent years prices for single family houses raised in the large urban areas and tourist resorts but, due to big land reserves, were stable or even declined in smaller urban and semi-urban as well as in rural areas. Price paths for condominiums are generally comparable to those of single family houses with the big difference, that over the last three years prices were raising in most of the regions.
Keywords: C31; R31; 330; Hedonic price; private property; direct index; indirect index